A study of the community school program of some pilot schools in the Philippines and implications for TURTEP schools of Ubol Teachers College, Thailand - Sedtheetorn, Preecha 1936- (s.n.], 1966)
This study identified the community school practices of the Philippines and the basic concepts, policies, practices, techniques and procedures connected with the movement. Implications for the TURTEP schools of Ubol Teachers College, Thailand were deduced from the findings.